Perubahan Pola Pengeluaran Makanan Masyarakat Indonesia Akibat Pandemi Covid-19 - Restu Asih Trianto (Jurnal Ecogen, 2021)
The Covid-19 had an impact on contraction of Indonesia’s GDP growth and declined income of many establishment and community. Declining economic conditions and activity restrictions are thought to have an impact on food expenditure pattern. This study aims to observe changes in food expenditure patterns before and after the Covid-19 pandemic by using the percentage of average expenditure on groceries, percentage of average expenditure on prepared food and tobacco, also the percentage of average expenditure on food.By using the paired test analysis method, (consist of paired t test and Wilcoxon signed-rank test), this study found that the Covid-19 pandemic did not have a significant effect on proportion of average food expenditure. However, the Covid-19 pandemic had a significant effect on food expenditure pattern, specifically the increase on percentage of average groceries expenditure and decrease on percentage of prepared food and tobacco.With an increase in the average expenditure on foodstuffs, it is suggested to the government to keep the supply of food ingredients available, especially in areas experiencing an increase in food expenditures. Then to business actors in the food and beverage sector, it is recommended to diversify products in the form of ready-to-cook food.